Aspectos qualitativos e quantitativos dos resíduos de construção e demolição (RCD) na cidade de Campina Grande - Araújo, Tafnys Rodrigues (2011)
This work aims to achieve the qualification and quantification of construction and demolition waste produced in the city of Campina Grande, PB. Data collection was performed in two stages, one for the qualitative and quantitative characterization to another. The qualitative characterization of the C&D waste was the plan to determine which materials are most commonly used in the construction process. The quantitative characterization of waste, aimed to define how much material is normally wasted per square meter in each work. The materials were found more easily as sand, bricks, ceramics, plaster, wood, iron, concrete debris and remains of stone. It was found that the city of Campina Grande (PB) are wasted approximately 26.5 kg of C&D waste per square meter of built work.